A comparative evaluation of semi-active control algorithms for real-time seismic protection of buildings via magnetorheological fluid dampers. (October 2021) - Şahin, Özge; Gökhan Adar, Nurettin; Kemerli, Muaz; Çaglar, Naci; Şahin, İsmail and Parlak, Zekeriya and Kükrek, Salih and Engin, Tahsin
Abstract: Semi-active vibration control is considered a powerful method in reducing the dynamic responses of buildings by using additional smart damping devices. In this study, magnetorheological (MR) dampers have been proposed as one of the semi-active control devices to mitigate the structural vibrations and improve the seismic performance of the structures. The performance of the MR dampers strongly depends on implemented controllers. Hence, the main purpose of this paper is to evaluate the efficiency of several semi-active control algorithms related to MR dampers for seismic control of civil building structures. A 5-story test structure is manufactured, and an MR damper is installed between the ground and the first floor. The performance of the semi-active control approach is experimentally evaluated on a shaking table under historical earthquake records. A neural network-based modeling approach is adopted in the inverse MR damper model for the current control. Three different control algorithms, namely Proportional-Integral-Derivative (PID), Sliding Mode (SMC) and Energy-based controller (EBC), are applied to the system in real-time. The shaking tests are also carried out on the structures with different natural frequencies by increasing the number of stories without changing the geometry and material properties of the 5-story building model. The results indicate that the SMC controller is the most effective control algorithm among all controllers in reducing the base shear force by 51%. Highlights: The different semi-active control approaches are applied to the structural systems equipped with an MR damper. The efficiency of the PID, sliding mode and energy-based controllers are investigated in predicting the damping force. The ANN inverse MR damper model is employed to predict the input current corresponding to the desired force. 5-8 story building models are experimentally investigated through the shaking table test under historical earthquakes. Experimental studies are conducted to investigate the effect of the controllers on the structural responses.